Feasibility of a novel colonoscope with extra-wide angle of view: a clinical study - Uraoka, Toshio; Tanaka, Shinji; Oka, Shiro; Matsuda, Takahisa; Saito, Yutaka; Moriyama, Tomohiko; Higashi, Reiji; Matsumoto, Takayuki (Endoscopy, 2015)
Background and study aims: Lesions may be missed during colonoscopy because of anatomical features such as mucosal folds. This feasibility study assessed the safety and efficacy of a novel colonoscope with extra-wide angle of view, which provides a simultaneous lateral-backward view to complement the forward view.Patients and methods: Consecutive patients undergoing colonoscopy using the prototype colonoscope were enrolled in this multicenter, single-arm study. The number of adverse events, and the first detection of adenomas during withdrawal by the lateral-backward view and the forward view were evaluated.Results: A total of 47 patients underwent colonoscopy examination to the cecum. The mean insertion and withdrawal times were 6.4 ± 4.9 minutes and 8.6 ± 4.2 minutes, respectively. Of 47 detected polyps, 28 adenomatous polyps were found (mean size 3.3 ± 3.1 mm). A total of 29 polyps (61.7 %) and 16 adenomatous polyps (57.1 %) were first detected with the lateral-backward view. The lateral-backward view first detected 5/6 adenomatous polyps (83.3 %) in the ascending colon and all (2/2) adenomatous polyps in the sigmoid colon. No adverse events occurred during the study.Conclusions: This exploratory study suggested that a novel colonoscope with extra-wide angle of view is safe and feasible, and has the potential to improve colorectal adenoma detection.Trial register: UMIN000016450